Input sourcing under supply chain risk: Evidence from U.S. manufacturing firms - Joaquin Blaum; Federico Esposito; Sebastian Heise (Federal Reserve Bank of New York, 2025)
We study the effect of climate risk on how firms organize their supply chains. We use transaction-level data on U.S. manufacturing imports to construct a novel measure of input sourcing risk based on the historical volatility of ocean shipping times. Our measure isolates the unexpected component of shipping times that is induced by weather conditions along more than 40,000 maritime routes. We first document that unexpected shipping delays induced by weather shocks have significant negative effects on importers' revenues, profits, and employment. We then show that more exposed firms actively diversify the risk of weather delays by using more routes and sourcing from more foreign suppliers, although their total imports decline. To rationalize these findings, we introduce shipping time risk into a general equilibrium model of importing with firm heterogeneity. Our quantitative analysis predicts substantial costs for the U.S. economy associated with different sources of supply chain risk.
Keywords: F10; F15; Q54; 330; supply chains; climate shocks; shipping time risk; input sourcing